Elastic strain energy control of the precipitate free zone around primary carbides in nickel base alloy 725. (November 2016) - Song, M.; Wen, J.-F.; Jiao, Z.; Was, G.S.
Abstract: Precipitate free zones (PFZs) are commonly believed to be controlled by either vacancy or solute depletion around sinks. This study shows that the PFZ around primary carbides (Nb, Ti)C is also influenced by stress field in alloy 725, which is a nickel base alloy hardened by γ″ precipitates. Finite element simulation suggests that the interaction energy between the local stress induced by primary carbides and the transformation strain of γ″ cause a bias in their nucleation. These observations show that in addition to diffusion, internal stress can significantly influence the nucleation of precipitates around sinks. Graphical abstract: